The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.17221/1741-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and dry matter digestion of some native and cultivated grasses in Mexico

Abstract: The objective of the study was to quantify differences in nutritive value, over four seasons, of native grasses such as <i>Bouteloua curtipendula, Bouteloua trifida, Brachiaria fasciculata, Chloris ciliata, Digitaria insularis, Leptochloa filiformis, Panicum hallii, Panicum obtusum, Paspalum unispicatum, Setaria grisebachii, Setaria macrostachya, Tridens eragrostoides, Tridens muticu</i>s and naturalized <i>chrus ciliaris</i> and <i>Rhynchelytrum repens</i> that are used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
3
7
0
1
Order By: Relevance
“…All herbage samples during the grazing period had adequate K levels to meet the optimum maintenance requirements for beef cattle (6 g/kg DM; NRC, 1996) and sheep (5 g/kg DM; NRC, 1985). Herbage biomass with sufficient K content to meet the maintenance requirements for beef cattle and sheep was also found by Ganskoop and Bohnert (2001), Ramirez et al (2009) in grasslands of northern Great Basin and Mexico, respectively, and by Roukos et al (2011a) in adjacent grasslands.…”
Section: Mineral Composition and Grass Tetany Indexmentioning
confidence: 90%
See 3 more Smart Citations
“…All herbage samples during the grazing period had adequate K levels to meet the optimum maintenance requirements for beef cattle (6 g/kg DM; NRC, 1996) and sheep (5 g/kg DM; NRC, 1985). Herbage biomass with sufficient K content to meet the maintenance requirements for beef cattle and sheep was also found by Ganskoop and Bohnert (2001), Ramirez et al (2009) in grasslands of northern Great Basin and Mexico, respectively, and by Roukos et al (2011a) in adjacent grasslands.…”
Section: Mineral Composition and Grass Tetany Indexmentioning
confidence: 90%
“…Thus, it can be assumed that there is an increased risk of Mg deficiency to occur in grazing livestock, a result also found by Roukos et al (2011a). Conversely, Ramirez et al (2009) reported that 13 grasses in Mexico had marginal sufficient levels of Mg to meet growing beef cattle requirements. Minson (1990) stated that seasonal variation of Mg content within species are relative small and Mg concentration in herbage is affected by its botanical composition and climatic conditions Suttle, 2010;Roukos et al, 2011a).…”
Section: Mineral Composition and Grass Tetany Indexmentioning
confidence: 94%
See 2 more Smart Citations
“…However, these evaluations may be complemented with studies of intake, ruminal fermentation and metabolites and hormones concentrations to more precisely establish dietary supplementation needs. As the rangelands mature, digestibility decreases because of decreased nitrogen and increased fibre and lignin contents (Ramı´rez et al 2009). These changes may be accompanied by a decrease in intake, ruminal ammonia and total volatile fatty acid (VFA) concentrations.…”
Section: Introductionmentioning
confidence: 99%